Chapter Introduction - Carretero, Mario; Perez-Manjarrez, Everardo (Taylor & Francis, 2025)
Providing the first volume-length exploration of the role that dialogue can play in history education classrooms, this book explores the socio-cultural, psychological, and digital dimensions of dialogic practice to promote research into historical thinking, historical consciousness, and critical thinking in educational settings. This book’s novel approach is in its analysis of dialogical processes in various international and intercultural educational contexts; chapters compare Israeli and Palestinian textbooks and classroom discussion and explore teachers’ challenges to shift monologic school culture, as well as approaches to enhancing dialogic practices both in US contexts and in several EU countries. Each case study provides an insight into the nature of dialogue as both shared historical inquiry and cultural practice. How can dialogue be promoted, and through what mechanisms? In what ways can dialogue contribute to democratic societies’ thriving and dealing with and overcoming conflicts about different views on the past? Ultimately, the book looks to foster a nuanced and complex understanding of history, prompting consideration of different perspectives and a collective approach to overcoming troubled pasts and trauma. Featuring a truly international set of contributions from established and emerging scholars, this book will appeal to scholars, researchers, and postgraduate students interested in the history of education, education policy and politics, and historiography more broadly. This book was made possible with the support of the EU project www.making-histories.eu (10108606), coordinated by the first author.